Regulatory Properties of an Inorganic Pyrophosphatase from the Photosynthetic Bacterium Rhodospirillum rubrum - Klemme, Jobst-Heinrich; Gest, Howard (Proceedings of the National Academy of Sciences - PNAS, 1971)
In Rhodospirillum rubrum, inorganic pyrophosphatase activity is observed in both the cytoplasmic and membrane fractions. The soluble enzyme accounts for about 80% of the total activity in crude extracts, and is the subject of this report. Zn2+is required for both activity and stability of the enzyme, which has a molecular weight of approximately 90,000 (gel-filtration determinations). The substrate is MgP2O7 2-, and free pyrophosphate (P2O7 4-) is a strong inhibitor. Kinetic experiments indicate homotropic interactions between substrate-binding sites; these interactions are influenced by Mg2+, which is an activator. At low concentrations of Zn2+, the pyrophosphatase is inhibited by NADH, NADPH, and MgATP; 50% inhibition occurs at 0.4-0.7 mM. These effects are reversed by high concentrations of Zn2+(10-4-10-3M). The nucleotides appear to inhibit activity of the ``native'' enzyme through an effect on Zn2+binding. The R. rubrum enzyme seems to be the first known example of a bacterial inorganic pyrophosphatase subject to allosteric regulation.